2010
DOI: 10.4103/0019-509x.63005
|View full text |Cite
|
Sign up to set email alerts
|

Quality of life among young women with breast cancer: Study from a tertiary cancer institute in south India

Abstract: The overall QOL in younger patients with breast cancer appeared to be good. The QOL and sexual function were marginally worse in the breast conservation group when compared to mastectomy group.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
67
22
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(101 citation statements)
references
References 13 publications
(16 reference statements)
4
67
22
1
Order By: Relevance
“…In many studies in breast cancer as well as other cancers it was seen that QOL has no or minimal correlation with socio demographic characteristics of patients. 9,12 However married women were found to be having significantly better QOL than unmarried. This could be because married women were feeling more secured and were getting more physical and mental support from their spouse and children.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In many studies in breast cancer as well as other cancers it was seen that QOL has no or minimal correlation with socio demographic characteristics of patients. 9,12 However married women were found to be having significantly better QOL than unmarried. This could be because married women were feeling more secured and were getting more physical and mental support from their spouse and children.…”
Section: Discussionmentioning
confidence: 99%
“…8 But contradictory to our result a study done by Dubashi et alshowed a good QOL in breast cancer patients. 9 This could be because their study was done among young patients who were long-term disease-free survivors.…”
Section: Discussionmentioning
confidence: 99%
“…One study showed no difference [14] while the other found that women who underwent BCS experienced greater psychological distress and marginally worse QOL [15], while another reported better QOL for patients undergoing BCS [16]. Pain and arm symptoms were also reported to be higher in the BCS group by various studies [16,17], while others reported higher incidence in the MRM group [18].…”
Section: Introductionmentioning
confidence: 99%
“…You'll become okay.^I say, BBut why this? Why are you giving me this drug versus this drug?^ (5) In decision making process related to treatment, the most common theme was letting the doctor decide as it was their profession to do so. However, few survivors were equally involved in their treatment based on research or through consultations with oncologists in the USA through Internet.…”
Section: Illness Treatment and Side-effectsmentioning
confidence: 99%
“…Lastly, it has focused on the medical treatments and ways of improvising on it. However, when it comes to the domain of psycho-oncology, studies have focused on Quality of Life [5] and handful of studies has focused on the psychosocial aspects of it [6,7]. It directly hints at the great dearth and the need for further research in psycho-oncology in India.…”
Section: Introductionmentioning
confidence: 99%